O diálogo entre ator e personagem no teatro espírita: a experiência espiritual e artística dos atores e atrizes do Grupo Espírita de Teatro Leopoldo Machado - Nascimento, Reginauro Sousa (2013)
The understanding of art as a pedagogical proposal which permits to the artist transmitting ideas, concepts and emotions in order to generate reflections and pointing ways to the development of society inside of an ethical and spiritualized perspective is the path that makes to us possible articulate art and spirituality on a dialogical and forming discussion to the becoming of the human being in his constant search to be more. The theater spiritist group Leopoldo Machado has offered us the necessary conditions to make this research possible, considering the specificity of theater it deals with and the goals attributed to its theatrical praxis: broadcasting the spiritism message, as a way to give spiritual sense to its audience and to work the self-transcendence. Before such elements already posed, it should be verified in what level the articulation between theater and spirituality if the self-transformation was indeed done by the actors who work with this field of knowledge. So I started from some initial questions that favor the deepening of these discussions: is there a dialogue between the actor and the character in the spiritist theater? The role played brings to the actor/actress reasoning about his/her own existence? The theater is a manifestation of spirituality or simply a mean of transmission of the message? From these reflections that were possible by the Freire cultural circles inside of the group universe a new question was born to the discussion: the spiritist theater group Leopoldo Machado is also a field for social human formation? The methodology elected to answer those proposed questions was the action-research because it makes possible a relation of bigger involvement where I have walked between the condition of researcher and subject of the very research run. The fundamental authors to this research are: BARBIER(2007);JOSSO (2004); FREIRE (1967, 1996, 1997, 2005) E AMUI (2005, 2009, 2011, 2012). Before the specificity of the questions debated it was necessary raising a theoretical referencial to this dialogue that involves art, education, spirituality and human formation. We bring some authors that permitted to us the approximation of spiritist knowledge and self-transcendence, theater and human formation, education and spirituality, highlighting among them:: KOUDELA( 1992); KARDEC ( 1997, 2002, 2003, 2008); DENIS (1997, 2008); FRANKL (1989) e BURNIER (2009)